Weitzman revisited: emission standards vs. taxes with uncertain control costs and market power of polluting firms - Clemens Heuson (Universität Augsburg, Institut für Volkswirtschaftslehre, 2008)
It is well known that uncertainty concerning firms' costs as well as market power of the latter have to be taken into account in order to design and choose environmental policy instruments in an optimal way. As a matter of fact, in most actual regulation settings the policy maker has to face both of these complications simultaneously. However, hitherto environmental economic theory has restricted to either of them when submitting conventional policy instruments to a comparative analysis. The article at hand takes a first step in closing this gap. It investigates the welfare effects of emission standards and taxes against the background of uncertain emission control costs and various degrees of the polluting firms' market power.
urn:nbn:de:bvb:384-opus4-711350
Keywords: D62; D89; L13; Q58; 330; Cournot oligopoly; external diseconomies of pollution; cost uncertainty; emission standard; emission tax; Umweltpolitik; Entscheidung bei Unsicherheit; Umweltauflage; Umweltabgabe; Ökosteuer; Umweltbehörde; Kosten; Marktmacht; Externer Effekt; Theorie